Information Literacy in the Workplace:A Cross-cultural Perspective - Wu, Yuhfen Diana (Tʻu shu kuan hsüeh yü tzŭ hsün kʻo hsüeh, 2012)
This cross-cultural study has two main purposes: to investigate how information literacy is perceived in the workplace and to discover how employees obtain information to carry out their jobs in an effective and timely fashion. This project applies a mix of research methods, including site visits, interviews, and a survey. More than 120 participants from forty companies were involved in this study. They were from a wide variety of industries in Taiwan and Silicon Valley, in Northern California, where many companies base offices or operations from around the world. Major obstacles in conducting cross-continent research are cost, time demands, scheduling, and adaptation to local culture. In this global economy, cross-cultural and cross-border research will help educators, such as librarians, understand the complexity of skills expected in the workplace. Much has been written on information literacy, yet very few can relate how information literacy is applied in the workplace. This primary study sheds some light to help academic librarians reposition themselves as researchers-educators integral to student success.